Effect of Spot Rate, Forward Rate, Inflation Rate And Interest Rate Against the Future Spot on the FX Market of Southeast Asia Region - Adam, Mohamad; Hadi, Isnur; Wahyuni, Yunita (Jurnal Manajemen, 2019)
This study aims to analyze empirically the influence of spot rates, forward rates, inflation rate and bungaterhadap rates on the futures spot on the Forex market of Southeast Asia Region. This study used samples of Indonesia, Malaysia, Singapore, Thailand and the Philippines during 2007-2016. The data used are obtained from Bank Indonesia and forexpros. The method of analysis used in this study is multiple regression analysis. The research results show that spot rate does not affect the future spot in Indonesia and Singapore, spot rate negatively affect the futures spot in Malaysia and Thailand, spot rate positively affect the future spot in Philippine country. The forward rate has no effect on the future spot in the countries of Indonesia, Malaysia, Singapore and Philippines, the exchange rate positively influences the future spot in Thailand. Inflation rate positively affects the future spot in Indonesia, Inflation rate has no effect on the future spot in Malaysia, Singapore and the Philippines. Interest rates negatively affect the future spot in the countries of Indonesia, Malaysia, Singapore and the Philippines. The interest rate has no effect on the future spot in Thailand. The results of research can be used for investors as a consideration in making investment decisions, especially on the Foreign Exchange Market.